1995
DOI: 10.1128/aem.61.12.4274-4277.1995
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Laccase in the White Rot Basidiomycete Phanerochaete chrysosporium BKM-F1767

Abstract: It has been widely reported that the white rot basidiomycete Phanerochaete chrysosporium, unlike most other white rot fungi, does not produce laccase, an enzyme implicated in lignin biodegradation. Our results showed that P. chrysosporium BKM-F1767 produces extracellular laccase in a defined culture medium containing cellulose (10 g/liter) and either 2.4 or 24 mM ammonium tartrate. Laccase activity was demonstrated in the concentrated extracellular culture fluids of this organism as determined by a laccase pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
3
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(96 citation statements)
references
References 38 publications
8
78
3
7
Order By: Relevance
“…The secretion of laccase by the ectomycorrhizal fungus T. terrestris was biomass-dependent as observed by Freitag and Morrell [18] in lignocellulolytic fungi. Residual glucose levels were demonstrated to be proportional to carbon source concentration, suggesting that secretion was not regulated by catabolic repression as previously suggested for Phanerochaete chrysosporium [6].…”
Section: Physiology Of Laccase Productionsupporting
confidence: 71%
See 2 more Smart Citations
“…The secretion of laccase by the ectomycorrhizal fungus T. terrestris was biomass-dependent as observed by Freitag and Morrell [18] in lignocellulolytic fungi. Residual glucose levels were demonstrated to be proportional to carbon source concentration, suggesting that secretion was not regulated by catabolic repression as previously suggested for Phanerochaete chrysosporium [6].…”
Section: Physiology Of Laccase Productionsupporting
confidence: 71%
“…Extracellular ammonium was completely depleted at 72 h of growth and mycelial dry weight became stationary at the same time. The level of exolaccase activity was proportional to the ammonium concentration in the medium as was observed with the production of laccase by ligninolytic fungi [6,7,24]. The results from changing the nutrient ratio indicate that nitrogen limitation a¡ected laccase production ( Table 2) and mycelial growth.…”
Section: Physiology Of Laccase Productionmentioning
confidence: 58%
See 1 more Smart Citation
“…Basidiomycetes typically produce multiple laccase isoforms [5,[23][24][25][26][27][28][29] and V. volvacea produces at least two protein bands with laccase activity when grown in submerged culture under different conditions [1]. Previous physiological studies have shown that, as in other basidiomycetes, laccase production by V. volvacea is induced by copper and by various aromatic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, P. chrysosporium is well reported for its high peroxidase enzyme (both LiP and MnP) activities associated with its lignin biodegradation. [24][25][26] Maximum laccase enzyme production of 70-80 U mL −1 by white rot fungus Panaeolus sphinctrinus using ABTS as substrate was also previously reported. 26,27 Our findings showed relatively much higher laccase production by L. elegans WDP2 in the minimal salt medium containing glucose and veratryl alcohol (as inducers).…”
Section: Selection Of Lignolytic Fungi For Biological Pretreatment Ofmentioning
confidence: 61%